The S-Layer Protein of the Anammox Bacterium Kuenenia stuttgartiensis Is Heavily O-Glycosylated - van Teeseling, Muriel C. F.; Maresch, Daniel; Rath, Cornelia B.; Figl, Rudolf; Altmann, Friedrich; Jetten, Mike S. M.; Messner, Paul; Schäffer, Christina; van Niftrik, Laura (Frontiers in Microbiology, 2016)
Anammox bacteria are a distinct group of Planctomycetes that are characterized by their unique ability to perform anaerobic ammonium oxidation with nitrite to dinitrogen gas in a specialized organelle. The cell of anammox bacteria comprises three membrane-bound compartments and is surrounded by a two-dimensional crystalline S-layer representing the direct interaction zone of anammox bacteria with the environment. Previous results from studies with the model anammox organism Kuenenia stuttgartiensis suggested that the protein monomers building the S-layer lattice are glycosylated. In the present study, we focussed on the characterization of the S-layer protein glycosylation in order to increase our knowledge on the cell surface characteristics of anammox bacteria. Mass spectrometry (MS) analysis showed an O-glycan attached to thirteen sites distributed over the entire 1591-amino acid S-layer protein. This glycan is composed of six monosaccharide residues, of which five are N-acetylhexosamine (HexNAc) residues. Four of these HexNAc residues have been identified as GalNAc. The sixth monosaccharide in the glycan is a putative dimethylated deoxyhexose. Two of the HexNAc residues were also found to contain a methyl group, thereby leading to an extensive degree of methylation of the glycan. This study presents the first characterization of a glycoprotein in a planctomycete and shows that the S-layer protein Kustd1514 of K. stuttgartiensis is heavily glycosylated with an O-linked oligosaccharide which is additionally modified by methylation. S-layer glycosylation clearly contributes to the diversification of the K. stuttgartiensis cell surface and can be expected to influence the interaction of the bacterium with other cells or abiotic surfaces.